Relationship between the blood perfusion values determined by laser speckle imaging and laser Doppler imaging in normal skin and port wine stains - Chen, Defu; Ren, Jie; Wang, Ying; Zhao, Hongyou; Li, Buhong; Gu, Ying (Photodiagnosis and photodynamic therapy, 2016)
•Comparison of simultaneous LDI and LSI outputs during PORH for the first time.•Relationship between simultaneous LDI and LSI outputs during PORH was non-linear.•Relationship between LDI and LSI outputs in port wine stains was linear.•Perfusion range should be considered when comparing LDI and LSI.•The measured skin characteristics should be considered when comparing LDI and LSI. Laser Doppler imaging (LDI) and laser speckle imaging (LSI) are two major optical techniques aiming at non-invasively imaging the skin blood perfusion. However, the relationship between perfusion values determined by LDI and LSI has not been fully explored. 8 healthy volunteers and 13 PWS patients were recruited. The perfusions in normal skin on the forearm of 8 healthy volunteers were simultaneously measured by both LDI and LSI during post-occlusive reactive hyperemia (PORH). Furthermore, the perfusions of port wine stains (PWS) lesions and contralateral normal skin of 10 PWS patients were also determined. In addition, the perfusions for PWS lesions from 3 PWS patients were successively monitored at 0, 10 and 20min during vascular-targeted photodynamic therapy (V-PDT). The average perfusion values determined by LSI were compared with those of LDI for each subject. In the normal skin during PORH, power function provided better fits of perfusion values than linear function: powers for individual subjects go from 1.312 to 1.942 (R2=0.8967–0.9951). There was a linear relationship between perfusion values determined by LDI and LSI in PWS and contralateral normal skin (R2=0.7308–0.9623), and in PWS during V-PDT (R2=0.8037–0.9968). The perfusion values determined by LDI and LSI correlate closely in normal skin and PWS over a broad range of skin perfusion. However, it still suggests that perfusion range and characteristics of the measured skin should be carefully considered if LDI and LSI measures are compared.